Highly enantioselective hiyama cross-coupling via Rh-catalyzed allylic arylation of racemic allyl chlorides - Fletcher, S (American Chemical Society, 2019)
Highly enantioselective Hiyama cross-coupling reactions have been achieved through rhodium(I)-catalyzed dynamic kinetic asymmetric transformations between aryl siloxanes and cyclic racemic allyl halides. This process affords valuable enantiomerically enriched aryl-substituted cyclic allyl products and is compatible with heterocyclic allyl chloride electrophiles.